Model validation of a high-speed flywheel energy storage system using power hardware-in-the-loop testing. (November 2021) - Karrari, Shahab; De Carne, Giovanni; Noe, Mathias
Abstract: Low-inertia power systems with a high share of renewables can suffer from fast frequency deviations during disturbances. Fast-reacting energy storage systems such as a Flywheel Energy Storage System (FESS) can help limit the frequency deviations by injecting or absorbing high amounts of active power, with almost no degradation concerns. But for an accurate evaluation of the benefits of using a FESS in power systems, an accurate and validated model is necessary, which not only reflects its advantages, but also shows the practical limitations of this technology, such as its losses, its auxiliary power requirements, and its limitations during the whole operational range. In this paper, an accurate model for a high-speed FESS is presented, and then experimentally validated by means of Power Hardware-in-the-Loop (PHIL) testing of a full-scale commercial high-speed FESS in several frequency deviation scenarios. The PHIL testing setup allows testing the FESS during extreme and realistic frequency deviation, including the major frequency disturbance of August 9, 2019, in the power system of the UK. In each scenario, the same inputs that are sent to the real FESS are also given to the FESS model, running in real time, for model validation, and an excellent match between the results of the real FESS and its model is observed. Moreover, the PHIL testing results demonstrate the quick response of the FESS, following a frequency deviation, and its compliance with the latest grid code requirements in Germany for frequency support. Highlights: A dynamic model for a high-speed Flywheel Energy Storage System (FESS) is presented. The model has been validated using power hardware-in-the-loop testing of a FESS. The FESS can reach the power set point in under 60 ms following frequency deviations. The maximum difference between the SOC of the model and the real FESS is 0.8%.